The Final Domino: Yasir Qadhi, Youtube, and Evolution - Moran, Glen (Zygon, 2021)
Debates around the compatibility or mutual exclusivity between Islam and evolution have received increasing academic attention in recent years. While research into Islam and evolution has often focused on the views of Muslim publics, a body of literature has emerged that has focused on the views of Muslim clerics and public figures. However, little research has been conducted about how prominent Muslim voices have used online platforms, such as YouTube, to promote their own views on Islam and evolution. This article explores the online video presentations of one such figure, namely, the American Muslim theologian Dr Yasir Qadhi. The article will demonstrate that Qadhi holds a relatively nuanced position on the compatibility between Islam and evolution, based on his understanding of the scientific consensus and Islamic scripture. Furthermore, it will also explore how Qadhi appeals directly to Muslims to reject many of the most common creationist arguments against evolution.